A network approach to addressing the needs of patients with incurable head and neck cancer and their families - Joanne M Patterson; Catriona R Mayland; Peter Bath; Michelle Lawton; Valerie Bryant; David Hamilton; Madina Hasan; Tony Stone; Richard Campbell; Annabel Crum; Linda Sharp (Health Technology Assessment)
Background Patients with incurable head and neck cancer have considerable unmet needs and complex symptom burden, with evidence of substantial geographical and/or socioeconomic inequalities. Accurate information on healthcare needs, resource utilisation and service provision in the last year of life is lacking. This places limits on service delivery planning and the development and testing of interventions to better meet needs. Our partnership spans three regions, which nationally have some of the highest rates of incurable head and neck cancer. Aims The overall aims were to (1) establish a palliative head and neck cancer partnership, (2) identify and evaluate routine incurable head and neck cancer data sources and utilise these to develop and address research priorities. Objectives O1. Develop a palliative head and neck cancer network within the North of England, representing a geographical area with high incidence of incurable head and neck cancer and palliative care needs. O2. Develop and refine research questions and priorities. O3. Engage with data providers to identify relevant data sets and specific data fields to understand the potential quality and utility of these to inform research priorities. Methods There were three interconnected work packages: WP1: A ‘snowballing’ approach to establish a network of clinicians, researchers, patient and public representatives, data architects and key stakeholders with an interest in head and neck cancer palliative care. WP2: A Delphi consensus process to develop and refine research questions and priorities, based on national guidance and systematic reviews of evidence gaps. WP3: Identification of national and local data sets and exploration of the potential data quality and utility, and associated information governance processes for access. Results WP1: A diverse network was established, encompassing members from a wide range of professions and patient/carer groups. WP2: The Delphi consisted of two rounds involving up to 66 participants. Consensus was reached on 12 research questions representing 4 key areas of prioritisation: service provision, symptom management, psychosocial support and information provision and communication. WP3: A range of national and local data sources were identified as having the potential to address the research priorities. A directory of data sources was developed. Working in an iterative way, data sets and relevant data fields were mapped to the 12 potential research priority areas to assess the applicability of using routine data to address these priorities. Limitations Approximately, one-third of participants in the Delphi process dropped out in round 2. Despite attempts to be flexible in our approach, retaining participants, particularly for patients and their families on a palliative care pathway, is challenging. Future work The established network and consensus exercise form the basis for future service evaluations and collaborative research. These will be based on gaps and priorities agreed by patients, their families and a range of other stakeholders. Conclusions The network has established a cross-sectoral collaboration for improving incurable head and neck cancer and a platform to identify 12 research priority areas. Utilising routine data to address these priorities remains a challenging area, and a range of methodological research approaches will be required to take this forward. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR135361. Plain language summary Background People with incurable head and neck cancer have very complex needs. The cancer and treatment cause severe difficulties in eating, speaking and breathing as well as pain, isolation and low mood. Because of this, individuals may need to use hospital or emergency care services more often, even towards the very end of their lives. Where individuals live, and how rich or poor the area is, affects whether those with head and neck cancer die at home or in hospital. The North of England has a relatively high number of people who die from head and neck cancer. What we did To learn more, help reduce variations in care, and improve experiences, we divided our work into three parts over 16 months. We established a North of England network of almost 150 people with interests, skills or experiences in this area. This included researchers, data specialists, healthcare workers and people with personal experience of head and neck cancer. We had three network meetings (two online and one face to face) and sent regular newsletters to keep the network updated about the work. We used a well-known method called a ‘Delphi process’ to work together and agree what research should be done. We gave network members a list of statements to rate and rank about potential areas. The process was repeated to gain majority agreement about which areas were the most important. We reviewed national and local information sources, for example, from hospitals. This was to find out what information was available about how head and neck cancer patients use healthcare services. There was not a lot of specific information about individuals who have incurable head and neck cancer. What will happen next We will use the results of the Delphi process to apply for more research funding to address priority areas.